Perceptions of Medical Students on Anatomy Education Environment in Medical Colleges by Aeemi: A Bi-Centre, Comparative Study - Qamar, Khadija; Malik, Amna Abbas; Kiran, Faiza; Yousaf, Wasif Ali; Asif, Masfah; Khalid, Laiba; Naqvi, Alisha Ali (Pakistan Armed Forces Medical Journal, 2024)
Objective: The aim of the study was to evaluate the different constructs of the Anatomy learning environment and the perception of medical students regarding the teaching facilities. Study Design: It was a thorough cross-sectional study. Place and Duration of Study: The study was conducted in a public sector and private sector medical college over a period of 6 months from Nov 2021 to Apr 2022. Methodology: It was a descriptive study in which a structured and self-administered questionnaire was distributed after obtaining consent from the subjects. For this study project, the best fit and validated model of The Anatomy Education Environment Measurement Inventory (AEEMI) was selected to evaluate the perception of medical students of educational climates with regard to teaching and learning anatomy. The sample size was 163 and 104 respectively. Data was collected from final year students of two medical colleges; one teaching Anatomy in a traditional manner and other teaching Anatomy via integration so we assumed that the Anatomy learning environment is different in both colleges. Results: The analysis of data revealed that out of 163 students from the traditional curriculum, 75(46.0%) had a positive area about Perceptions of Anatomy Knowledge Relevance and 61(37.4%) had a positive area about Students’ Positive Perceptions of Anatomy Teachers. Moreover, 104 students from integrated curriculum (63.8%) had a positive area about Students Negative Perceptions of Anatomy Teachers and 36(22.1%) had a positive area about Students’ Perception of Anatomy Subject Mastery. In addition, 48(29.4%) out of 163 had positive areas about Students’ Perception of Anatomy Learning Resources. Students learning Anatomy via integration had positive perceptions in all five domains of inventory. Conclusions: The data reveals that out of 163 students, 56(34.22%) had a positive perception of the constructs of the anatomy learning environment. Total 67(61%) students who were studying Anatomy via integration had positive perceptions about their Anatomy teachers, whereas 80(49%) students of traditional curriculum were of the view that Anatomy educators need to improve their teaching methodologies. Nearly 55(50%) students of integrated curriculum were satisfied that they have mastered the subject and 63(57%) were happy about novel and updated learning resources.